(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2014)
Acute post streptococcal glomerulonephritis (APSGN) remains a common cause of acute nephritis in children. Acute poststreptococcal glomerulonephritis usually occurs as sporadic cases, occasionally an unusually high incidence of acute nephritis has been recorded. In our country we need to recognize, document and analyze epidemic attacks of acute post streptococcal glomerulonephritis. Then we can plan for its prevention. We have reported here a cluster of cases of APSGN prevailed in a family of a rural setting of southeast part of Bangladesh which was admitted in a subdistrict level hospital and also noticed that total admitted cases of APSGN in that hospital was more during the month of notification in comparison to other months but were not able to identify all the cases of APSGN prevailing in that area. Prophylactic antibiotic treatment is advisable in epidemic conditions and to household contacts of index cases in communities where the prevalence of the disease is high. It is expected that there are some cluster of cases of APSGN in different regions of our country during different period that is to be notified. Public awareness regarding prevention and early treatment of scabis is required. DOI: http://dx.doi.org/10.3329/cmoshmcj.v13i3.21034